NEOLIBERAL DENIAL OF FREEDOM AND DEMOCRACY - Оrdenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The modern understanding of freedom is based on the neoliberal concept of negative freedom refers to economic subjects, that is, economic entities whose activities are aimed at realizing their own economic interests. The theoretical basis of the study was socio-philosophical and political science developments, as well as political and economic researches of H. Arendt, Z. Bauman, D. Bell, I. Berlin, F. Engels, K. Marx, D. North, P. Rosanvalon, A. Smith, J. Stiglitz, H. Hoppe, D. Harvey, and others. The aim and tasks are to substantiate the neoliberal denial of freedom and democracy in a globalized world, determining the causes of this process and outlining the possible consequences for society on the socio-philosophical basis. Research methods are the dialectical method in combination with general philosophical methods and methodological approaches (systematic, objectivity, ascent from the abstract to the concrete, correspondence, and relativity). Research results. At the heart of the neoliberal denial of freedom and democracy there is the postmodern denial of modern culture, the rejection of its values. Postmodern consciousness decrowns the mind, rational authorities, in particular, the political and legal, democratic ideals of Modern. The modern understanding of freedom is based on the concept of negative freedom, which is understood as exclusively economic freedom realized on the principle of laissez-faire, that is, non-interference in the sphere of economic relations. But by promoting postmodern "freedom from everything", the adherents of negative freedom not only destroy the sphere of the positive freedom, but also level the existence of the negative one, i.e. private. The neoliberal agenda, mixing the spheres of private and public thus denies positive and negative freedom and the principle of laissez-faire - the classical principles of liberalism, a democratic form of government, the nation-state, and so on. This agenda is absolutely hostile to anything that contradicts the utilitarianism of market logic. Discussion. According to D. Bell, capitalist society drifts to one of the forms of the economy controlled by the state – to a bureaucratic society. It is obvious that in the course of the development of capitalist society there is a disturbance of the balance between economy and politics, when, on the contrary, the economy drifts to the totalitarian subjugation of the state, and the state begins to perform useful but economically destructive functions. Соnclusion. Neoliberal factors in the denial of democracy include the gradual disappearance of the political against the background of the assertion of the economy when politics becomes only an appendage of the economy. It follows that neoliberalism is not a new form of freedom and democracy. On the contrary, the neoliberal agenda denies freedom, classical liberalism, democratic form of governance, the nation-state, and so on.